Extreme control of light in metamaterials: Complete and loss-free stopping of light - K. L. Tsakmakidis; Hess, O. (Physica B: Condensed Matter, 2012)
We present an overview of recent advances within the field of slow- and stopped-light in metamaterial and plasmonic waveguides. We start by elucidating the mechanisms by which these configurations can enable complete stopping of light. Decoherence mechanisms may destroy the zero-group-velocity condition for real-frequency/complex-wavevector modes, but we show that metamaterial and nanoplasmonic waveguides also support complex-frequency/real-wavevector modes that uphold the light-stopping condition. A further point of focus is how, by using gain, dissipative losses can be overcome in the slow- and stopped-light regimes. To this end, on the basis of full-wave finite-difference time-domain (FDTD) simulations and analytic transfer-matrix calculations, we show that the incorporation of thin layers made of an active medium, placed adjacently to the core layer of a negative-refractive-index waveguide, can fully remove dissipative losses in a slow- or stopped-light regime where the effective index of the guided lightwave remains negative. © 2012 Elsevier B.V. All rights reserved.
cited By 15